Working Memory in the Service of Executive Control Functions - Mansouri, Farshad A.; Rosa, Marcello G. P.; Atapour, Nafiseh (Frontiers in Systems Neuroscience, 2015)
Short-term memory is a crucial cognitive function for supporting on-going and upcoming behaviours, allowing storage of information across delay periods. The content of this memory may typically include tangible information about features such as the shape, colour or texture of an object, its location and motion relative to the body, or phonological information. The neural correlate of these short-term memories has been found in different brain areas involved in organizing perceptual or motor functions. In particular, neuronal activity in different prefrontal areas encodes task-related information corresponding to short-term memory across delay periods, and lesions in the prefrontal cortex severely affect the ability to hold this type of memory. Recent studies have further expanded the scope and possible role of short-term memory by showing that information of abstract entities such as a behaviour-guiding rule, or the occurrence of a conflict in information processing; can also be maintained in short-term memory and used for adjusting the allocation of executive control in dynamic environments. It has also been shown that neuronal activity in the dorsolateral prefrontal and orbitofrontal cortices encodes information about such abstract entities. These findings suggest that the prefrontal cortex plays crucial roles in organizing goal-directed behaviour by supporting various mnemonic processes that maintain a wide range of information in the service of executive control of on-going or upcoming behaviour.